Evaluation and Temporal-Spatial Deconstruction for High-Quality Development of Regional Marine Economy: A Case Study of China - An, Dong; Shen, Chunlei; Yang, Lin (Frontiers in Marine Science, 2022)
The high-quality development of the marine economy has become a realistic choice to stimulate the vitality of regional economic growth and achieve the goal of building a powerful nation in the marine economy. This study constructs an evaluation index system from efficiency, coordination, innovation, sustainability, openness, and shareability to analyze the high-quality development level and temporal-spatial heterogeneity of China’s regional marine economy from 2010 to 2018. Methods used in this paper are entropy, kernel density estimation, and partial spatial autocorrelation analysis. The results are shown as follows: (1) The high-quality development level of China’s regional marine economy shows a slow fluctuating and upward trend, coordination, sustainability, and innovation are the primary driving forces. The ranking of the three marine economic circles in the development quality of the marine economy is Eastern> Southern>Northern, the ranking of coastal provinces is Guangdong> Shanghai> Shandong> Zhejiang> Fujian> Tianjin> Jiangsu> Liaoning> Hainan> Hebei> Guangxi. The primary driving forces for Guangdong, Shanghai, Shandong, and Zhejiang leading other coastal areas are openness, efficiency, innovation, and sustainability respectively; (2) the temporal differentiation of China’s regional marine economy shows a dynamic evolution process that is obvious in the early stages, alleviating in the middle stage, and balance in the later stage; (3) the spatial zoning types and high-quality development paths of 11 coastal provinces are determined based on spatial differentiation: Shanghai and Zhejiang are high-value congregate types and named as demonstration regions, which should build global marine center cities with deepening regional cooperation and high-standard opening-up; Shandong and Guangdong are high-value discrete types and named as key engine regions, which should enhance the international competitiveness of the marine industry with scientific and technological innovation; Tianjin, Hebei, and Liaoning are low-value congregate types and named as potential zooming regions, which should improve the efficiency of marine resources utilization with regional cooperation; Jiangsu, Fujian, Hainan, and Guangxi are low-value discrete types and named as land-sea coordination regions, which should build a modern and characteristic marine industrial system coordinated with land and sea.